The Effect of Relaxation Therapy with Aromatherapy on Community Anxiety during the Covid-19 Pandemic in Cikaret Village, West Java in 2020 - Saputri, Milla Evelianti; Lubis, Rosmawaty; Pamela, Devieni Naulia (STRADA : Jurnal Ilmiah Kesehatan, 2021)
The results of the study stated that 54% of adolescent anxiety levels are in the high category because adolescents are said to be unstable in facing unexpected conditions. Providing relaxation therapy with aromatherapy is able to reduce anxiety in the community. This study aims to determine the effect of giving relaxation therapy with aromatherapy on public anxiety during the COVID-19 pandemic. This study used a quasi-experimental pre-post-test one group design. The sample in this study amounted to 30 people, consisting of adolescents 12-24 years. The sampling technique used total sampling. The research instrument consisted of the HARS anxiety questionnaire and aromatherapy. The data were analyzed using non-parametric tests, namely paired samples T-Test. The results showed that there was a significant effect on anxiety scores before and after being given relaxation therapy with aromatherapy with a sig. (2-tailed) of 0.000 <0.005.